Chapter 10 Rethinking urban resettlement and displacement from the perspective of 'home' in the interruption and uncertainty brought about by the COVID-19 pandemic - Huchzermeyer, Marie (Taylor & Francis, 2021)
This chapter reflects on contributions in this book, providing an outlook on displacement into a future rendered uncertain by the Covid-19 pandemic. The contemporary urban political economy has implications for housing. This justifies a focus on human needs articulated through the concepts of dwelling and home. These allow displacement to be explored as 'un-homing'. The human right to adequate housing incorporates the main dimensions of home and un-homing. However, these are seldom reflected fully in housing policy and implementation. As recommended by the UN with reference to this right, most countries adopted Covid-19 emergency regulations with measures to protect housing. In South Africa, the resulting stay on evictions was violated, the state also planning new displacement through temporary relocations intended to decongest informal settlements in response to the pandemic. Home intrusion and privacy violations through smart technology are further forms of un-homing sharpened by responses to the pandemic. Future research can productively bring this lived experience to bear on policy.